2018
DOI: 10.29271/jcpsp.2018.04.304
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Of Chronic Kidney Disease Patients On The Basis Of Referral To Nephrologist: A One-year Follow-up Study

Abstract: There is no difference on the outcome of dialysis patients on the basis referral to nephrologist. Factors affecting overall mortality in both groups were financial status, metabolic acidosis, and temporary access for dialysis. Most of the patients were referred late to the nephrologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our results indicate that the vast majority of our patients have anaemia. Similar results were reported by Anees et al, 2018 who found that 91.2% of kidney failure patients had anaemia [9]. Indeed, the endogenous erythropoietin deficiency, the uremic inhibitors and the shortened red blood cells survival are the main cause of anaemia in haemodialysis patients [10].…”
Section: Resultssupporting
confidence: 84%
“…Our results indicate that the vast majority of our patients have anaemia. Similar results were reported by Anees et al, 2018 who found that 91.2% of kidney failure patients had anaemia [9]. Indeed, the endogenous erythropoietin deficiency, the uremic inhibitors and the shortened red blood cells survival are the main cause of anaemia in haemodialysis patients [10].…”
Section: Resultssupporting
confidence: 84%
“…In this study, major cause of ESRD was diabetes mellitus and hypertension which is similar to local and international studies but has changed since last decade locally when chronic GN was the leading cause of ESRD. 9,12,13 It may be due to better infection control measures that the prevalence of ESRD due to infectious GN has decreased and at the same time our dietary habits have changed leading to more metabolic syndrome and prevalence of Diabetes Mellitus. Anemia is an important predictor of morbidity and mortality for the dialysis patients.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, troponin value was high in AMI patients and no correlation was found between IMA and troponin. In (23,24).…”
Section: Discussionmentioning
confidence: 99%